2017
DOI: 10.1002/jcb.26314
|View full text |Cite
|
Sign up to set email alerts
|

MAPK8 regulates chicken male germ cell differentiation through JNK signaling pathway

Abstract: The study aims to analyze the key signaling pathways in regulating the process of embryonic stem cells (ESCs) differentiation into spermatogonial stem cells (SSCs). We explored the specific regulating mechanisms of C-Jun amino-terminal kinase (JNK) signaling in this process. Interference/overexpression of MAPK8 allows the JNK signaling pathway to be blocked/activated. In Retinoic acid (RA) induced in vitro differentiation assays, the expression of germ cell marker genes, cvh, c-kit, integrin α6 and integrin β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…However, high levels of LncPGCAT‐1 induced JNK phosphorylation. Moreover, JNK signaling was also activated during PGC formation in vivo (Abdellah et al, 2003; Wang, et al, 2017), confirming that LncPGCAT‐1 regulates PGC formation by activating MAPK‐JNK signaling through ILF3.…”
Section: Resultsmentioning
confidence: 90%
“…However, high levels of LncPGCAT‐1 induced JNK phosphorylation. Moreover, JNK signaling was also activated during PGC formation in vivo (Abdellah et al, 2003; Wang, et al, 2017), confirming that LncPGCAT‐1 regulates PGC formation by activating MAPK‐JNK signaling through ILF3.…”
Section: Resultsmentioning
confidence: 90%
“…To further clarify the functions of miRNA in various groups, we conducted KEGG pathway enrichment analysis. We found that the miRNA in the Cluster1 is significantly enriched in the SSC formation of related signaling pathways, such as Wnt signaling pathway [ 12 ], JAK-STAT signaling pathway [ 13 ], and MAPK signaling pathway [ 14 ] ( Figure 1(d) ), showing that among the four miRNA clusters, miRNAs in the Cluster1 were more likely to participate in the SSC formation process. Meanwhile, we found these signaling pathways are regulated by miRNA302d target genes.…”
Section: Resultsmentioning
confidence: 99%
“…Many researches have elucidated the momentous role of MAPK8 in bovine myocyte development, inflammation, and disease treatment. ,, It is worth noting that MAPK8 performs these functions mainly through the JNK pathway. For instance, the study of Wang et al revealed that MAPK8 regulates chicken male germ cytodifferentiation through the JNK signaling pathway . MAP3K11, also known as mixed-spectrum kinase 3 (MLK3), acts as a positive regulator of the c-Jun N-terminal kinase (JNK) signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the study of Wang et al revealed that MAPK8 regulates chicken male germ cytodifferentiation through the JNK signaling pathway. 54 MAP3K11, also known as mixedspectrum kinase 3 (MLK3), 55 acts as a positive regulator of the c-Jun N-terminal kinase (JNK) signaling pathway. 56 The JNK pathway mainly regulates various physiological processes such as inflammatory response, cytodifferentiation, cell proliferation, and cell apoptosis.…”
Section: ■ Discussionmentioning
confidence: 99%